Student Achievement at TIMSS and PISA Tests as a Guideline for Modifying Mathematics Curriculum - Јasmina Milinković; Bojan Lazić (University of Belgrade, Teacher Education Faculty, 2018)
Student achievement is primarily conditioned by the quality of the curriculum and the teaching process. From the perspective of the modern conception of mathematics literacy, the efficacy of the basic mathematics education in Serbia is reflected in student achievement at international TIMSS and PISA tests. A comparative analysis of the TIMSS and PISA contents and our curriculum has shown that the content of our curriculum for basic mathematics education requires improvement. Moreover, a comparative analysis of mathematics curricula for the lower grades of primary school that are currently in force in many countries (Finland, Japan, South Korea, Hong Kong, Russia, Singapore, Slovenia) with the mathematics curricula in Serbia has revealed chronological and contentrelated discrepancies. The authors of the paper point out the disproportion in student achievement at TIMSS and PISA tests for the purpose of looking for plausible explanations and exploring the ways of improving mathematics teaching at primary school level. The paper offers a suggestion for modernisation of the curriculum for the primary school grades 1 to 4 by enlarging the current curriculum and introducing new content relevant for further education. Drawing upon the results of the research conducted to this day, the authors recommend a propaedeutic approach in the preparation of students for the adoption of formal knowledge, from the 5th grade onwards. If this approach is implemented, we can reasonably expect better effects of learning of the aforementioned content for grades 5 to 8 of primary school.